Lichen community structure and richness in three mid-elevation secondary forests in Costa Rica - Cordero Solórzano, Roberto A. (2021)
Introduction: Lichen diversity, community structure, composition and species abundance have been used as indicators of the integrity and ecological continuity of tropical forest ecosystems. Objectives: To assess corticolous lichen species composition, diversity, and ecological importance of three forested stands differing in time of abandonment as indicators of how passive restoration influences the lichen community assemblage. Methods: We surveyed individual lichens on tree stems of a reference old secondary forest and a young secondary forest (50 and 14-year-old natural regeneration after pasture abandonment, respectively), and in a 35-year-old exotic cypress tree plantation, in the oriental Central Valley, in Orosí, Costa Rica. Standard diversity, similarity indexes, and the importance value index were calculated. An NMDS analysis was performed on the community structure parameters and in a presence-absence matrix. Results: We found 64 lichen species in 25 families with 42, 21, and 23 species, and 20, 10, and 15 families, in the young and old secondary forests, and the cypress plantation, respectively. Cryptothecia sp. possessed the highest importance across sites. More than 87 % of the species are rare. The combined IVI of the top three families were: 36, 48.5, and 74.8 % in the young and old forests and the Cypress plantation sites, respectively. Overall, Arthoniaceae is in the top three families. The young forest had the highest species richness, but the old forest presented the best evenness. Similarity and diversity indexes suggest a particularly low resemblance in the lichen communities but a smooth gradient differentiation between the three forests, which was confirmed by the NMDS test. The homogeneity test identified great differences in ecological importance and composition. Conclusions: This region contains a distinctive assemblage of species resulting in a strong community differentiation by site, reflecting the influence of ecophysiological and microclimatic factors that define lichen establishment and survival and suggesting a great regional beta diversity, within a fragmented landscape. Greater connectivity and passive restoration strategies resulted in greater diversity and a more heterogeneous community structure on both forests than the corticolous community of the abandoned plantation. Protection of forest fragments will maximize the integrity of future forests.